2010
DOI: 10.1007/bf03326186
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of two-phase fluid flow and oil slick transport in estuarine water

Abstract: ABSTRACT:Oil spills is one of the most important hazards in the estuarine and coastal water. In recent decades, engineers try to predict the status of oil slick to manage the pollution spreading. The prediction of oil slick transport is carried out mainly by means of numerical models. In the current study, the development and application of a two-phase fluid flow model to simulate oil transport in the marine environment are presented. Different transport and fate processes are included in the developed model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Preexisting information on coastal resources and prioritized protection areas allow for a faster response and better distribution of protection and cleanup efforts, thereby facilitating appropriate coastal management (Santos and Andrade, 2009). In the last three decades, the movement of oil spills on the water surface has been studied extensively (Wang and Shen, 2010), resulting in two-dimensional (2D) oil spill models of advection and spreading (Nagheeby and Kolahdooza, 2010). At present, models are commonly used to study oil trajectories for planning or assessment purposes (Galt, 1994, Kankara et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Preexisting information on coastal resources and prioritized protection areas allow for a faster response and better distribution of protection and cleanup efforts, thereby facilitating appropriate coastal management (Santos and Andrade, 2009). In the last three decades, the movement of oil spills on the water surface has been studied extensively (Wang and Shen, 2010), resulting in two-dimensional (2D) oil spill models of advection and spreading (Nagheeby and Kolahdooza, 2010). At present, models are commonly used to study oil trajectories for planning or assessment purposes (Galt, 1994, Kankara et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the effects of wind on high-rise buildings, bridges and other architectural structures is of critical importance and is an integral part of the structural design process (American Society of Civil Engineers [ASCE] 2005). Also, wind profile simulation is very important in environmental pollution transportation modeling (Nagheeby and Kolahdoozan 2010;Abdullah et al 2007;Freddy Kho et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The ability of biosurfactants to emulsify hydrocarbon-water mixtures has been very well documented (Oberbremer et al, 1990;Francy et al, 1991;Zhang and Miller, 1992;Goyal et al,2008). This property has been demonstrated to increase hydrocarbon degradation significantly, thus it is potentially useful for oil spill management (Atlas and Bartha, 1992;Banat 1993;Bonin et al, 1994;Husseien et al, 2009;Nagheeby and kolahdoozan, 2010). Haghighat et al (2008) reported indigenous isolate from crude oil storage tank in Tehran Refinery, Tehran, Iran, Bacillus licheniformis and Bacillus subtitlis for MEOR which produce lipopetide biosurfactant.…”
Section: Introductionmentioning
confidence: 99%